The blue supergiant progenitor of the supernova imposter AT 2019krl - Andrews, Jennifer; Kreckel, Kathryn; Santoro, Francesco (The astrophysical journal, 2021)
Extensive archival Hubble Space Telescope, Spitzer Space Telescope, and Large Binocular Telescope imaging of the recent intermediate-luminosity transient, AT 2019krl in M74, reveal a bright optical and mid-infrared progenitor star. While the optical peak of the event was missed, a peak was detected in the infrared with an absolute magnitude of M4.5 μm = −18.4 mag, leading us to infer a visual-wavelength peak absolute magnitude of −13.5 to −14.5. The pre-discovery light curve indicated no outbursts over the previous 16 yr. The colors, magnitudes, and inferred temperatures of the progenitor best match a 13-14 Me yellow or blue supergiant (BSG) if only foreground extinction is taken into account, or a hotter and more massive star if any additional local extinction is included. A pre-eruption spectrum of the star reveals strong Hα and [N II] emission with wings extending to ±2000 km s−1. The post-eruption spectrum is fairly ﬂat and featureless with only Hα, Na I D, [Ca II], and the Ca II triplet in emission. As in many previous intermediate-luminosity transients, AT 2019krl shows remarkable observational similarities to luminous blue variable (LBV) giant eruptions, SN 2008S-like events, and massive-star mergers. However, the information about the pre-eruption star favors either a relatively unobscured BSG or a more extinguished LBV with M > 20 Me likely viewed pole-on.
Gesehen am 31.03.2021